PENGARUH KOMPETENSI, MOTIVASI, KOMITMEN ORGANISASI PADA KINERJA DEWAN KOMISARIS BPR SEKABUPATEN GIANYAR - Purwanti, Ni Wayan Dian; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
The purpose of this study was to determine the effect on the performance of the Board of Commissioners Competence BPR All Gianyar regency, to determine the effect of motivation on the performance of the Board of Commissioners of BPR All Gianyar and to determine the influence of Organizational Commitment on the performance of the Board of Commissioners of BPR All Gianyar regency. The samples used in this study were 52 respondents using sampling methods are porpusive sampling method. Data collected through documentation and questionnaires. Technical analysis of the data used in this research is multiple linear regression. Based on the test results show that the Competence (X1), motivation (X2) and Organizational Commitment (X2) effect on the performance of the board of commissioners of rural banks Entire Gianyar.
Keywords: Competence, Motivation, Organizational Commitment, Performance, BOC, RB.